Pyrone Synthesis from Renewable Sources: Easy Preparation of 3‐Acetoxy‐2‐oxo‐2H‐pyran‐6‐carboxylic Salts and their Derivatives as 3‐Hydroxy‐2H‐pyran‐2‐one from C6 Aldaric Acids. Issue 2 (9th January 2020) - Leonardi, Gabriella; Li, Jiemeng; Righetti, Grazia Isa C.; Truscello, Ada M.; Gambarotti, Cristian; Terraneo, Giancarlo; Citterio, Attilio; Sebastiano, Roberto
Abstract : 2‐Pyrones are compounds present in several natural products and represent interesting building blocks for the preparation of intermediates in organic syntheses. For these reasons, many different preparation protocols have been developed for the synthesis of pyrone moieties. In this work, a green approach toward the synthesis of those compounds starting from C6 aldaric acids has been investigated. These products are an interesting and versatile class of poly functional C6 units coming from renewable sources. In this paper, we report a green procedure based on a reaction with acetic anhydride under different pH conditions to convert mucic acid and glucaric acid salts into the 3‐acetoxy‐2‐oxo‐2 H ‐pyran‐6‐carboxylic acid salts and their derivatives. The salts, in the presence of hydrochloric acid, are quantitatively converted into the corresponding 3‐hydroxy‐2‐oxo‐2 H ‐pyran‐6‐carboxylic acid, which afforded 3‐hydroxy‐2 H ‐pyran‐2‐one in very high yield by further thermal decarboxylation. Crystal structure of the five membered ring lactone intermediate is reported. Abstract : A green approach to the synthesis of 3‐acetoxy‐2‐oxo‐2 H ‐pyran‐6‐carboxylated derivatives from bio‐derived C6 aldaric acids has been investigated. All the six carbon atoms present in the aldaric acid are preserved. For the first time mucic acid lactone salt has been isolated and fully characterized.